O Abrigo do Passadeiro, Palaçoulo (Miranda do Douro) : Um caso de estudo de gravuras rupestres dos inícios do holocénico no nordeste de Portugal - Sanches, Maria de Jesus; Teixeira, Joana de Castro (Portvgalia : Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da FLUP, 2018)
Taking the Passadeiro rock engravings study case as a starting point we will synthetically discuss the chronology of the abstract and subnaturalistic rock art within this region (Northeast of Portugal /Northwest of the Iberian Meseta). At the center of our discussion there are two core questions, they are: i) the chronological and cultural context of “devil claw” type carvings, as well as the other linear and thin motifs graphically associated with them; ii) the fact that, in Passadeiro, those motifs (“devil claw” carvings associated to thin linear risks) are overlapped by a subnaturalistic drawing of a red deer, typologically attributable to the beginnings of the Holocene. Questions will also be brought up concerning the regional prehistoric occupation from the end of the Tardiglaciar period to the middle of the Holocene.